The Effects of the Use of 3D Printing Technology on the Entrepreneurs’ Operational Effectiveness - Al-Dmour, Rand; Surakji , Muath; Ahmed Amin, Eatedal (Jordan Journal of Business Administration, 2023)
This paper examines the effects of the use of 3D Printing Technology (3DPT) applications on entrepreneurs’ operational effectiveness. For this purpose, a study model based on the relevant previous studies was proposed. The data for this research was collected using a self-administered questionnaire given to 161 respondents. The target respondents were those employed in entrepreneurial companies in Jordan and the data was analyzed using simple and multiple regression techniques. The findings indicate that the extent of 3DPT being used by entrepreneurial companies in Jordan was considered to be moderate at this stage and it varied among them in terms of their size and business experience. Further, all integrated effectiveness indicators (time, cost, quality, competitiveness and management processes) were significantly influenced by the level of the use of 3DPT; the most important effectiveness indicators were found to be time, cost and quality due to the business environment context found in Jordan.